Polityka medialna jako teoria i praktyka regulacyjna - Michalczyk, Stanisław (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Media Policy as a theory and practice of regulation The article focus on theoretical and practical aspects of contemporary media policy, finding the phenomena as an activity of creation and implementation of general principles and rules regarding the operation of media organizations and mediated public communication. In fact media policy is based on two different levels of regulation: government and governance. The author discusses the activities of key actors of media policy and regulation. He claims that within the internal affairs an important role in Media Policy play the regulatory authorities. Among the key actors of European Media Policy are such institutions as the Council of Europe, OSCE and European Union, while on a global scale operate especially ITU, WTO, ONZ and UNESCO. Key words: media policy, regulation, government, governance, actors of the media policy